HISTORY OF THE DEVELOPMENT OF DENTISTRY AS A SCIENCE AND PRACTICE (The Role of Exact Sciences in the Era of Modern Development, 2024)
Article is devoted to the history of the development of dentistry as a science and practice. Particular attention is paid to the stages of development of this area, as well as the history of dentistry in the East, in particular in Central Asia.